Analisis Dampak Pandemi Covid-19 Terhadap Pelatihan Dan Pengembangan Terhadap Produktivitas Kinerja Karyawan Pada Kantor Balai Teknik Perkeretaapian Kelas II Wilayah Sumatera Bagian Utara - Rifki Fikrianda; Sri Ramadhani (LPPM Universitas Labuhanbatu, 2021)
Human resources are the most important asset for the company because they are the drivers of the company's activities. The pandemic that has hit in recent years is certainly very influential and has an impact on employees, especially on the ongoing process of training and development activities. The process of training and development activities during a pandemic as it is today is very different from before, training and development before a pandemic can be said to run smoothly and without constraints and maximally because it is carried out directly and interacts with each other between resource persons and development training participants while during a pandemic as it is today the process of training and development activities is carried out online/online which is remote, of course, without any direct interaction between individuals with each other. Actually, the problem is the level of understanding of participants in digesting any material conveyed by the speaker of training and development and the other side of the saturation level of participants will be higher as well because they feel bored and sometimes there is often a disruption of the internet network that is less stable resulting in the process of training and development activities become hampered and disrupted. However, this activity must be carried out and intensively carried out because this activity aims to improve the skills of employees in their respective fields so that when the skill or ability of employees increases productivity, employee performance will also increase so that the company can get maximum benefits in accordance with the expected from the beginning.